B Cells Modulate Mucosal Associated Invariant T Cell Immune Responses - Salerno-Goncalves, Rosangela; Rezwan, Tasmia; Sztein, Marcelo B. (Frontiers in Immunology, 2014)
A common finding when measuring T cell immunity to enteric bacterial vaccines in humans is the presence of background responses among individuals before immunization. Yet the nature of these background responses remains largely unknown. Recent findings show the presence in uninfected individuals of mucosal associated invariant T (MAIT) cells that mount broad spectrum immune responses against a variety of microorganisms including Mycobacterium tuberculosis and enteric bacteria such as E. coli and Salmonella. Therefore, we investigated whether MAIT immune responses to intestinal bacteria might account for the background responses observed before immunization. Here we measured MAIT immune responses to commensal and enteric pathogenic bacteria in healthy individuals with no history of oral immunization with enteric bacteria. We found that MAIT cells were activated by B cells infected with various bacteria strains (commensals and pathogens from the Enterobacteriaceae family, but not by uninfected cells. These responses were restricted by the non-classical MHC-related molecule 1 (MR1) and involved the endocytic pathway. The quality of these responses (i.e., cytokine profile) was dependent on bacterial load but not on the level expression of MR1 or bacterial antigen on B cell surface, suggesting that a threshold level of MR1 expression is required to trigger MAIT activation. These results provide important insights into the role of B cells as a source of antigen presenting cells to MAIT cells and the gut immune surveillance of commensal microbiota.